2014
DOI: 10.1111/pin.12198
|View full text |Cite
|
Sign up to set email alerts
|

Class III/IV POU transcription factors expressed in small cell lung cancer cells are involved in proneural/neuroendocrine differentiation

Abstract: One-third of lung malignancies demonstrate a proneural/neuroendocrine phenotype or type of differentiation. However, it has not been clearly elucidated how proneural/neuroendocrine differentiation is controlled in lung cancers. We recently demonstrated that the POU3F2 gene plays a significant role in proneural/neuroendocrine differentiation of lung cancers. Because class III POU genes (POU3F1, POU3F2, POU3F3, and POU3F4) and class IV POU genes (POU4F1, POU4F2, and POU4F3) share similar properties in neural dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…The study drew on three cases of DIPNECH meeting the minimum pathologic criteria proposed by Marchevsky et al [15]: ≥3 bronchioles with ≥5 neuroendocrine cells (NECH) and ≥3 carcinoid tumorlets. Clinical data (gender, age at onset, smoking status, surgical procedure, and follow-up information) and pathological findings were retrieved from the hospital archives and retrospectively reviewed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study drew on three cases of DIPNECH meeting the minimum pathologic criteria proposed by Marchevsky et al [15]: ≥3 bronchioles with ≥5 neuroendocrine cells (NECH) and ≥3 carcinoid tumorlets. Clinical data (gender, age at onset, smoking status, surgical procedure, and follow-up information) and pathological findings were retrieved from the hospital archives and retrospectively reviewed.…”
Section: Methodsmentioning
confidence: 99%
“…POU transcription factors play essential roles in organ development and cellular differentiation. POU-III/IV induce expression of neuroendocrine markers (synaptophysin, neural cell adhesion molecule 1, and chromogranin A), act as regulators of neuroendocrine differentiation in lung cancer cells, and are proneural transcription factors (ASCL1 and neuroD) [15,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TTF1 inhibits the transforming growth factor‐β‐mediated epithelial‐to‐mesenchymal transition in lung adenocarcinoma cells; moreover, myosin binding protein H, which inhibits cell migration through inhibitory interaction with Rho kinase 1, has been reported to be a transcriptional target of TTF1 . Recently, we reported that TTF1 is directly induced by POU3F2 (which is specifically expressed in SmCC cells), FOXA1, and FOXA2 and that POU3F4 and POU4F2 also strongly induce TTF1 expression . TTF1 is an important transcription factor for fetal diencephalon morphogenesis, and POU3F2 plays crucial roles in the development of the endocrine hypothalamus and posterior pituitary gland .…”
Section: Regulation Of the Neuroendocrine Phenotype Via Specific Tranmentioning
confidence: 98%
“…The class III POU transcription factors co‐localize and interact each other . We recently reported that all class III/IV POU transcription factors are specifically expressed in SmCC cells, in which they induce the expression of not only neuroendocrine markers (i.e., synaptophysin, neural cell adhesion molecule 1, and chromogranin A) but also proneural transcription factors (i.e., ASCL1 and ND1), and also mutually induce the other class III/IV transcription factors . Notably, POU3F4 and POU4F2 cause morphological changes (i.e., cytoplasmic miniaturization, spindle shaping, and thin cytoplasmic projection formation) in large cell lung carcinoma cells .…”
Section: Regulation Of the Neuroendocrine Phenotype Via Specific Tranmentioning
confidence: 99%